Parent-adolescent communication and adolescent mental health outcomes: A systematic review - Saraswati, Dewa Ayu Sri; Mujahidah, Zakiyah; Komalasari, Oom (Lentera Perawat, 2026)
Background: Parent-adolescent communication is an essential family process that may influence adolescent mental health outcomes, particularly during a developmental period marked by emotional, social, and behavioral transitions. Poor communication within the family may increase adolescents’ vulnerability to depression, anxiety, emotional difficulties, behavioral problems, suicidal ideation, and low psychological well-being. Objective: This systematic review aimed to synthesize current evidence on the relationship between parent-adolescent communication and adolescent mental health outcomes. Methods: This review followed the Preferred Reporting Items for Systematic Reviews and Meta-Analyses 2020 guideline. Literature searches were conducted in Scopus, ProQuest, PubMed, and SAGE Journals, with the final search completed in March 2026. Eligible studies were primary empirical articles published between 2015 and 2026 in English or Indonesian, involving adolescents aged 10–19 years or samples predominantly composed of adolescents. Study selection, quality appraisal, and data extraction were conducted independently by two reviewers, with disagreements resolved through discussion or consultation with a third reviewer. The Joanna Briggs Institute Critical Appraisal Checklists were used to assess methodological quality. A narrative synthesis was performed because of heterogeneity in study designs, populations, communication measures, and mental health outcomes. Results: Of 10,803 records initially identified, 10 studies were included in the final synthesis. The evidence showed that positive, open, consistent, and culturally sensitive parent-adolescent communication was associated with better adolescent mental health outcomes. Poor communication was linked to higher depressive symptoms, anxiety, emotional distress, behavioral problems, family conflict, and reduced treatment engagement. Communication also supported emotional disclosure, help-seeking behavior, parental care management during suicidal crises, and engagement in family-centered mental health interventions. Cultural context, digital exposure, parental mental health literacy, and structural barriers influenced the quality of communication. Conclusion: Parent-adolescent communication is a key protective factor for adolescent mental health. Family-centered prevention and clinical interventions should strengthen parental listening, emotional validation, mental health literacy, crisis response, and culturally responsive communication.